LEGAL POLICY ON NON-ORGANIC FIREARMS OWNERSHIP FOR CIVILIANS IN INDONESIA: SAAD AL-DZARI’AH PERSPECTIVE - Rasyid, Sausan Apriati (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2024)
This study aims to better know and understand how the procedure of owning non-organic firearms for civilians to create legal policies that apply in Indonesia. Some things the author has said about the rules applied and how they relate to Islamic law related to the theory of Sadd Al-Dzari'ah which is still new enough to be associated with the title the author conveys. The approach taken in this study is normative juridical using literature or document studies, which are managed through secondary data sources in the form of primary legal materials, secondary legal materials, and tertiary legal materials whose type of research is normative law. The results of the study concluded that the legal aspects of firearm ownership based on the investigation of firearms, munitions, and explosives as stated in Police Regulation Number 1 of 2022 regarding the classification of weapons and how the permit procedures must be met for prospective owners of non-organic firearms for special police, PPPNS, Civil Service Police Units, Security Forces or interests for self-defense. Referring to the theory of Sadd Al-Dzariah, Dzari'ah is one of the postulates in establishing the law despite disputed use. There are benefits from the ownership and use of firearms but if the use does not follow the requirements and can cause stability for the owner, then the ideal form of ownership of firearms, based on the theory of the purpose of law provides certainty, justice and benefit for human problems explains the ideal legal framework and law enforcement policy.